Biazeotropy in three-phase mixtures - L. A. Serafimov; T. V. Chelyuskina; E. A. Sharonova (Тонкие химические технологии, 2010)
Evolution of diagrams of biazeotropic three-phase mixture methyl tert-butyl ether - water at high pressure was considered.